The Effect of EMDR and CBT on Low Self-esteem in a General Psychiatric Population: A Randomized Controlled Trial - Griffioen, Brecht T.; van der Vegt, Anna A.; de Groot, Izaäk W.; de Jongh, Ad (Frontiers in Psychology, 2017)
Although low self-esteem has been found to be an important factor in the development and maintenance of psychopathology, surprisingly little is known about its treatment. This study investigated the effectiveness of Eye Movement Desensitization and Reprocessing (EMDR) therapy and Cognitive Behavioural Therapy (CBT), regarding their capacities in enhancing self-esteem in a general psychiatric secondary health care population. A randomized controlled trial with two parallel groups was used. Participants were randomly allocated to either 10 weekly sessions of EMDR (n=15) or CBT (n=15). They were assessed pre-treatment, after each session, post treatment and at 3 months follow-up on self-esteem (Rosenberg Self-Esteem Scale and Credibility of Core Beliefs), psychological symptoms (Brief Symptom Inventory), social anxiety and social interaction (Inventory of Interpersonal Situations). The data were analysed using repeated measures ANOVA for the complete cases (n=19) and intention-to-treat (n=30) to examine differences over time and between conditions. Both groups, EMDR as well as CBT, showed significant improvements on self-esteem, increasing two standard deviations on the main parameter (RSES). Furthermore, the results showed significant reductions in general psychiatric symptoms. The effects were maintained at 3 months follow-up. No between-group differences could be detected. Although the small sample requires to exercise caution in the interpretation of the findings, the results suggest that, when offering an adequate number of sessions, both EMDR and CBT have the potential to be effective treatments for patients with low self-esteem and a wide range of comorbid psychiatric conditions. This study was registered at www.trialregister.nl with identifier NTR4611.